Notes for the history of Peruvian Law. A case of assistance policy in favor of the parties of the corregimento of Huaylas in the XVIII century - Valverde Gonzáles, Manuel Enrique (2011)
A historical retrospective of the social indigenous movements in the 18th century in the County of Huaylas, within the context of tax reforms introduced by the colonial administration with the aim of obtaining greater revenues for the Spanish crown, and the abuses committed by the intermediary bureaucracy in charge of tax collection. This article analyzes the legal repercussions of the action promoted by the leaders of the doctrine of the County of Huaylas before the political administration of the Viceroyalty of Peru with the aim of obtaining financial aid from the funds of the Census Bank of the County, to assist the indigenous peoples of said province.